4'-hydroxycinnamaldehyde from Alpinia galanga (Linn.) induces human leukemic cell apoptosis via mitochondrial and endoplasmic reticulum stress pathways - Ratana Banjerdpongchai (2018)
Rhizomes of Alpinia galanga (Linn.) or 'Kha' in Thai are used in food and as folk medicine in South and Southeast Asia. The aims of this study were to identify the mechanism of cell death of human leukemic HL-60 and U937 cells induced by 4'-hydroxycinnamaldehyde (4'-HCA) isolated from A. galanga. 4'-HCA was cytotoxic to both cell lines in a dose-dependent manner (p<0.05) as demonstrated by MTT assay. Apoptosis induced by 4'-HCA was demonstrated by a variety of methods: visualization of propidium iodide (PI)-stained cells under fluorescence microscope, detection of subdiploid cells by PI-staining and flow cytometry, and assay of active caspase-3 using a specific fluorogenic substrate. 4'-HCA-treated cells (10 and 50 μg/ml for 4 h) showed significant increase in reactive oxygen species production and decreased mitochondrial transmembrane potential as detected by dichlorohydrofluorescein diacetate and 3,3'-dihexyloxacarbocyanine iodide respectively, together with flow cytometry. The apoptotic death involved cytochrome c release, increase in Bax level and concomitant decreases in levels of Bcl-2 and Bcl-xL (using Western blotting), and elevation in cytosolic and mitochondrial Ca2+contents (using compartment-specific fluorescent Ca2+dyes). These results indicate that 4'-HCA induces apoptosis of human leukemic cell through a combination of mitochondrial and ER stress pathways.